Protective Effects of Pentoxifylline and Nimodipine on Acoustic Trauma in Guinea Pig Cochlea - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2011)
Objective: To examine the protective effects of the vasodilator and hemorheologically active drug pentoxifylline and the calcium channel blocker nimodipine on the cochlea after acoustic overexposure in guinea pigs. Methods: Eighteen guinea pigs were used. The animals were divided into 5 groups: 1) control, 2) acoustic trauma, 3) nimodipine plus acoustic trauma, 4) pentoxifylline plus acoustic trauma, and 5) pentoxifylline plus nimodipine plus acoustic trauma. Nimodipine was given to the guinea pigs 3 mg/kg intraperitoneally in a single dose; pentoxifylline was given 150 mg/kg in a single dose intraperitoneally. A gunnery range was used to create acoustic trauma. The auditory brainstem response of each guinea pig was determined first; then, the animals were killed, and their cochleas were examined under an electron microscope. Results: In the acoustic trauma group, negative auditory brainstem response potentials were seen as was well-adjusted cellular damage to the organ of Corti. In the pentoxifylline group, near-normal auditory brainstem response recordings and organ of Corti histologic findings were found. Organ of Corti damage was seen in the pentoxifylline plus nimodipine plus acoustic trauma group. Conclusion: We determined that pentoxifylline was highly protective against noise, but nimodipine was not. Also, pentoxifylline and nimodipine, when used together, increased damage to the organ of Corti.
Keywords: Acoustic trauma; Cochlea; Nimodipine; Pentoxifylline; INDUCED HEARING-LOSS; INNER-EAR DISEASE; BLOOD-FLOW; CALCIUM-CHANNEL; MOUSE COCHLEA; INJURY; OVERSTIMULATION; POTENTIALS; ANTAGONIST; HYPOXIA